Naphthalene induced hemolysis in a glucose 6 phosphate dehydrogenase deficient neonate - A case report - Kamal, Murtaza; Arya, Sugandha; Shriyan, Rhea; Chellani, Harish (Indian Journal of Child Health, 2017)
Glucose-6-phosphate dehydrogenase (G6PD), a critical enzyme in the hexose monophosphate pathway, is a key component in the antioxidant mechanism of all cells, particularly erythrocytes. Its deficiency may manifest in the neonatal period in the form of severe hyperbilirubinemia. Hemolysis in neonate may occur de novo or be precipitated by stressors such as oxidant drugs or naphthalene. We report a case of 3 days old, G6PD deficient neonate, with naphthalene induced hemolysis, requiring exchange transfusion.